Enhancing Nahwu Mastery: Implementation of the Card Sort Method in Madrasah Aliyah - Wachida Muhlis; Muassomah Muassomah; Ibnu Hajar; Hasmiati Hasmiati; Rusdiana Rusdiana; Andi Muammar Kareba; Nurfadillah Nurfadillah (ALSINATUNA, 2024)
The Card Sort method is one of the learning methods that encourages students to actively participate in learning. This study aims to describe the implementation of the card sort method in Nahwu learning, map the supporting and inhibiting factors of the application of the card sort method in Nahwu learning and explore student perceptions of the card sort method in Nahwu learning at Madrasah Aliyah Al-Hidayah Karangploso Malang. This research applies qualitative descriptive research method. Data collection using observation, and documentation. The data analysis used is in the form of Interactive models Miles, Huberman, and Saldana, which include the stages of data condensation, data presentation, and conclusions. The implementation of the card sort method in Nahwu learning at Madrasah Aliyah  Al-Hidayah Karangploso Malang shows positive potential. In the implementation of this learning, of course, there are supporting factors and inhibiting factors. Students respond positively to the use of this method. Students find learning Nahwu with the card sort method fun, helps understand the material faster, and increases their active involvement in the learning process